Radiation therapy for people with cancer: what do written information materials tell them?. (10th August 2015) - Smith, S.K.; Yan, B.; Milross, C.; Dhillon, H.M.
Abstract : This study aimed to compare and contrast the contents of different types of written patient information about radiotherapy, namely (1) hospital radiotherapy departments vs. cancer control organisations and (2) generic vs. tumour‐specific materials. A coding framework, informed by existing patients' information needs literature, was developed and applied to 54 radiotherapy information resources. The framework comprised 12 broad themes; cancer diagnosis, general information about radiotherapy, treatment planning, daily treatment, side effects, self‐care management, external radiotherapy, internal radiotherapy, impact on daily activities, post‐treatment, psychosocial health and other content, such as a glossary. Materials produced by cancer organisations contained significantly more information than hospital resources on diagnosis, general radiotherapy information, internal radiotherapy and psychosocial health. However, hospital materials provided more information about treatment planning, daily treatment and the impact on daily activities. Compared to generic materials, tumour‐specific resources were superior in providing information about diagnosis, daily treatment, side effects, post‐treatment and psychosocial health. Information about internal radiotherapy, prognosis and chronic side effects were poorly covered by most resources. Collectively, hospital and cancer organisation resources complement each other in meeting patients' information needs. Identifying ways to consolidate different information sources could help comprehensively address patients' medical and psychosocial information needs about radiotherapy.